Social capital, education, and subjective well-being in Ecuador - Núñez-Naranjo, Aracelly; Morales-Urrutia, Ximena; Simbaña-Taipe, Luis (Frontiers in Sociology, 2024)
The study examines the interaction between social capital, education, and subjective well-being in Ecuador, highlighting its impact on economic development. The study aims to understand the situation of social capital and subjective well-being and how the identified factors explain the impact on subjective well-being in the Ecuadorian population, using a descriptive and analytical approach with information from the World Value Survey database of waves 6 and 7. The main results show a significant relationship between social capital and subjective well-being, with positive influences such as justice and union membership, and negative effects of public administration and media. In conclusion, the importance of strengthening social capital and improving public services and communication to promote the well-being of the Ecuadorian population is emphasized.